The Influence Of Organizational Behavior And Job Satisfaction On Employee Performance At PT Bosowa Asuransi - Fahri, Muhammad; Sari, Yulia Indah Permata; Teguh, Saeful Hadi; Rakhman, Sitti (Sean Institute, 2025)
This study aims to analyze the influence of organizational behavior and job satisfaction on employee performance at PT Bosowa Asuransi. Using a quantitative approach, data were collected through questionnaires distributed to 70 respondents. The data analysis techniques employed included multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results revealed that organizational behavior and job satisfaction positively and significantly influence employee performance both partially and simultaneously. The coefficient of determination of 90.6% indicates that organizational behavior and job satisfaction collectively explain the variability in employee performance, while the remaining 9.4% is influenced by other factors not examined in this study. This study recommends strengthening organizational culture, improving employee welfare, and conducting regular evaluations to enhance overall employee performance